The Trihalomethanes Formation in Water Distribution Systems: The Laboratory Analog Experiments and Analysis - Lv Mou; Li Hongyan; Wang Menglin (2010 International Conference on Challenges in Environmental Science and Computer Engineering : proceedings, Wuhan, China, 6-7 March 2010, 2010)
Chlorination of drinking water leads to the formation of trihalomethanes (THMs) that has been proved have adverse health effects on humans. Research on this subject has been continued and new epidemiological and toxicological studies have been conducted. In this paper, authors investigate and analyze factors affecting THMs formation in pipe networks by conducting corresponding experiments on a close small-scale water supply system in lab. The main factors affecting THMs formation such as chlorine and humic acid concentration was measured and controlled in the system for identifying their effects. According the experiment results, solutions of minimizing the amounts of THMs in municipal distribution systems are posted.